Pelaksanaan Kegiatan Sosial di Penampungan Anjing untuk Meningkatkan Kesehatan Anjing Terlantar - Evando Deswison; Bryan Tjan; Jason Junus Saujana; Ferdy Anthonius; Christian Siregar (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The health and welfare of stray dogs remains a significant problem in Indonesia, primarily due to malnutrition, limited healthcare, and low public awareness of responsible pet ownership. This community service activity was carried out at the Maria Stray Home dog shelter, South Tangerang, with the aim of improving the physical and emotional well-being of shelter dogs while raising awareness among the surrounding community. The implementation method of the activity was carried out through three main approaches, namely dog ​​hygiene care through bathing activities, fulfilling nutritional needs through providing nutritious food according to a structured schedule, and counseling to the community about animal welfare and the importance of adoption. The activity was carried out through preparation, implementation, and evaluation stages with an observational and reflective approach together with the shelter manager. The results of the activity showed an improvement in the physical condition of the dogs, marked by increased cleanliness of their fur and skin and better activity responses after regular care and feeding. Emotionally, the dogs showed a decrease in aggressive and anxious behavior observed through an increase in positive responses to human interaction. The outreach activities also resulted in increased community involvement and acceptance of the shelter's existence. This activity demonstrates that structured and sustained community interventions can significantly contribute to improving the welfare of shelter dogs and strengthening public awareness and support for animal welfare efforts.